2017
DOI: 10.1002/1873-3468.12637
|View full text |Cite
|
Sign up to set email alerts
|

An experimental comparison of human and bovine rhodopsin provides insight into the molecular basis of retinal disease

Abstract: Rhodopsin is the visual pigment that mediates dim-light vision in vertebrates and is a model system for the study of retinal disease. The majority of rhodopsin experiments are performed using bovine rhodopsin; however, recent evidence suggests that significant functional differences exist among mammalian rhodopsins. In this study, we identify differences in both thermal decay and light-activated retinal release rates between bovine and human rhodopsin and perform mutagenesis studies to highlight two clusters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 70 publications
3
21
1
Order By: Relevance
“…One of the compounds that was shown to better photosensitize rhodopsin is Chl‐e6, which properties were characterized experimentally and theoretically: Chl‐e6 absorption is set at 644 nm (1.92 eV) in water and, after fast relaxation in the S 1 state, fluorescence is found at 668 nm (1.86 eV) in ethanol . Our CASPT2 results, also corroborated by available experiments, indicate that bovine rhodopsin absorbs at ca . 493 nm (2.52 eV).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…One of the compounds that was shown to better photosensitize rhodopsin is Chl‐e6, which properties were characterized experimentally and theoretically: Chl‐e6 absorption is set at 644 nm (1.92 eV) in water and, after fast relaxation in the S 1 state, fluorescence is found at 668 nm (1.86 eV) in ethanol . Our CASPT2 results, also corroborated by available experiments, indicate that bovine rhodopsin absorbs at ca . 493 nm (2.52 eV).…”
Section: Resultssupporting
confidence: 75%
“…Rhodopsin is activated by light with an absorbance maximum at 500 nm, in the cyan part of the spectrum . For this reason, a different visual transduction pathway has been proposed for some deep‐sea fish species, reached only by low energy light, mostly in the red part of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we decided to focus on sites 119, 123, and 124, two of which (119, 123) are thought to have functional effects via the TM3-TM5 microdomain ( Stojanovic et al, 2003 ). Altogether, these sites are located in close proximity to several important structural regions known to affect MII stability, such as N302 of the NPxxY motif, the TM3-TM5 microdomain involving sites 122–211, as well as the all- trans retinal binding pocket ( Choe et al, 2011 ); Figure 3A ), suggesting that residues at these positions may form novel structural interactions that could compensate for the destabilizing loss of the E122-H211 hydrogen bond ( Stojanovic et al, 2003 ; Morrow et al, 2017 ). Consistent with the entrenchment of compensatory mutations at coevolving sites ( Talavera et al, 2015 ; Pollock et al, 2012 ; Shah et al, 2015 ), using ancestral reconstruction we found that sites 119, 122, 123, and 124 are strongly conserved as the LxxEIA (L119-E122-I123-A124; referred to as ‘LEIA’) and FxxINS motifs (F119-I122-N123-S124; ‘FINS’) within tetrapod and Characiphysi RH1, respectively, likely since the most recent common ancestor of each lineage, where LEIA is predicted as the ancestral Osteichthyes motif ( Figure 3B ; Tables 1 , Supplementary files 1 , 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Natural high-altitude variants from both Andean and Himalayan catfish RH1 may have therefore been specifically targeted by selection to accelerate RH1 kinetic rates at high altitudes. In contrast, other mutations at conserved positions within the visual opsins can increase protein stability and consequently decelerate the kinetic rates of dark-and active-state rhodopsin decay (Imai et al 1997;Stojanovic et al 2003;Xie et al 2003;Dungan and Chang 2017;Morrow et al 2017;Yue et al 2017). Moreover, rhodopsin mutations affecting these kinetic rates often also produce pleiotropic effects altering the spectral absorbance (λ MAX ) of rhodopsin (Gozem et al 2012;Luk et al 2016;Yue et al 2017).…”
Section: Rhodopsin Kinetics At High Altitudesmentioning
confidence: 99%